Aqueous/Aqueous Micro Phase Separation: Construction of an Artificial Model of Cellular Assembly - Sakuta, Hiroki; Fujimoto, Tadashi; Yamana, Yusuke; Hoda, Yusuke; Tsumoto, Kanta; Yoshikawa, Kenichi (Frontiers in Chemistry, 2019)
To artificially construct a three-dimensional cell assembly, we investigated the availability of long-duration microdroplets that emerged near a critical point in an aqueous two-phase system (ATPS) with the hydrophilic binary polymers, polyethylene glycol (PEG) and dextran (DEX), as host containers. We found that erythrocytes (horse red blood cells; RBCs) and NAMRU mouse mammary gland epithelial cells (NMuMG cells) were completely and spontaneously entrapped inside DEX-rich microdroplets. RBCs and NMuMG cells were located in the interior and at the periphery of the droplets at PEG/DEX = 5%:5%. In contrast, the cells exhibited opposite localizations at PEG/DEX = 10%:5%, where, interestingly, NMuMG cells apparently assembled to achieve cell adhesion. We simply interpreted such specific localizations by considering the alternative responses of these cells to the properties of the PEG/DEX interfaces with different gradients in polymer concentrations.